International tax agreements. - United Nations. Department of Economic Affairs (Lake Success [s.n.], 1948)
Irregular
"United Nations publications. Sales no.: 1948.XVI.2; 1951.XVI.
At head of title: United Natios. Dept. of Economic Affairs. Fiscal Division.
Keywords: Taxation, Double -- Periodicals; Tax evasion -- Periodicals